Predisposal factors leading to early re-amputation among diabetic patients who underwent minor amputation: Underlying factors for early subsequent amputations - Gürsan, Onur; Çeltik, Mustafa; Türemiş, Cihangir (Journal of Surgery and Medicine, 2023)
Background/Aim: Prolonged wound complications and the possibility of reoperations are significant outcomes following minor amputations. As time progresses after the initial surgery, re-amputations become more prevalent. Contrary to prevailing beliefs, the incidence of early amputations remains consistent. Additionally, it is widely acknowledged that the first 6 months following the initial surgery pose the highest risk period for reoperation. This retrospective clinical study aims to investigate the risk factors contributing to ipsilateral re-amputation procedures within 6 months of the initial minor amputation. Methods: A retrospective cohort study was conducted involving amputee patients from 2008 to 2020. Patients with traumatic events, musculoskeletal tumors, prior major amputations, and those who underwent soft tissue procedures such as debridement, incision, drainage, or secondary closure were excluded. Patients who had undergone preoperative lower limb arterial Doppler ultrasound and whose initial preoperative laboratory records were accessible were included. The total cohort comprised 168 patients, comprising 57 women and 109 men. The mean follow-up duration was 1.5 years (range: 1.1–3.2 years). Patients who underwent ipsilateral re-amputation were categorized into two groups based on the timing of the subsequent surgery. The first group comprised 110 (65.5%) patients who underwent ipsilateral re-amputation 6 months after the initial amputation, while the second group encompassed 58 (34.5%) patients who underwent ipsilateral re-amputation within 6 months of the initial amputation. Results: Among the 168 patients, 58 (34.5%) experienced ipsilateral re-amputation within 6 months of their initial minor amputations, while 64.5% underwent re-amputation surgery after the initial 6 months. The absence of peripheral arterial disease was not linked to early re-amputations (P=0.001). Although the mean C-reactive protein values (80.30 mg/dL and 84.26 mg/dL for groups 1 and 2, respectively) did not display significance between the groups (P=0.40), the group undergoing amputation within 6 months demonstrated significance with elevated serum white blood cell mean levels (10.44 mcL and 11.96 mcL for groups 1 and 2, respectively; [P=0.004]). Moreover, lower hemoglobin levels (11.41 g/dL and 10.77 g/dL for groups 1 and 2, respectively) were associated with re-amputation within the initial 6 months following the initial surgery (P=0.024). Conclusion: The study underscores that the incidence of re-amputation after minor amputations in diabetic patients is comparably high, as has been reported in recent literature. While the selection of the initial amputation level remains pivotal, and not all patient-specific factors were examined in this study, the research brings attention to specific laboratory values and the vascular status of the diabetic limb as crucial considerations for surgeons prior to the initial surgery.